Measuring the antecedents of turnover intentions: Perspectives of private healthcare employees in a less-developed economy - Victor Kwarteng Owusu (LLC "CPC "Business Perspectives", 2021)
This study sets out to investigate the antecedents of turnover intentions, using the private healthcare employees in an emerging economy (Ghana) as a benchmark. Even though myriad studies have been conducted on the aforementioned topic, yet, there are scant investigations on how employees of private healthcare institutions relate towards turnover intentions, specifically in a developing economy context. Therefore, this study draws on extant literature and subsequently proposes a hypothetical argument on the effect of training satisfaction, benefits and incentives on employee turnover intentions as well as resistance to change while establishing the nexus between turnover intentions and resistance to change. Both paper and web-based (online) questionnaires were gauged from employees of private healthcare organizations in Ghana. Data were analyzed by partial least square structural equation modeling (PLS-SEM) on a sample of 544 employees of private healthcare institutions. The findings indicate that training satisfaction, benefits and incentives have a positive impact on an employee’s turnover intentions. Moreover, employee’s resistance to change is influenced by both training satisfaction and benefits and incentives. Further, the investigation established that employee’s resistance to change influences employee turnover intentions. The thoughtful mechanisms of how the running of private healthcare institutions in Ghana can be enhanced are expanded by the empirical results obtained through how employees can be satisfied by training and the application of rewards to reduce turnover. Moreover, administrators of private healthcare organizations are forewarned of the implications of employees’ resistance to change and its effect on employee turnover intentions. Acknowledgment This study was supported by Tomas Bata University in Zlín, through IGA/FaME/2020/003 “Training and development programs and the consequence on employee’s commitment, satisfaction and organizational performance: analysis from Czech public service sector”.